A Systematic Review of Quantitative and Qualitative Research on Divorce Factor - Maryam Eskafi Noghani; Farideh Gorgidge; Ali Hojjati Shargh (Gonabad University of Medical Sciences, 2021)
Background: Divorce has always been one of the five main issues in the country and one of the criteria for community health. Therefore, this study aimed to systematically review quantitative and qualitative research on the factors affecting divorce. Methods: The research community included all the quantitative and qualitative articles published from 2006 to 2016, which regarded the causes of divorce. A total number of 70 quantitative and qualitative studies were selected and reviewed individually. Results: The findings showed that the highest share of the individual and personality trait factors is the variable of addiction (14.28% in quantitative research and 32.3% in qualitative research), followed by verbal and physical violence (28.84% in quantitative research and 21.42% in the qualitative section). The most frequent economic variables in both research categories were economic problems (10.71%) and unemployment (14.7%). Among the social factors, the interference of families and people around them had the highest share and contributed to 17.85% and 21.42% of the quantitative and qualitative research, respectively. Besides, among the cultural factors studied, idealism and the positive imagery of the consequences of divorce with the frequency of 14.7% in quantitative and quantitative research, and the negative effects of media with the frequency of 10.71% in qualitative research had the highest percentages, compared with other variables. Conclusion: Based on the findings, we conducted an analysis using the Boudon model to determine the final pattern of divorce, however, it was impossible to design a comprehensive model.